Analog circuit design robust design, sigma delta converters, RFID - Casier, Herman; Steyaert, Michiel 1959-; Roermund, Arthur H. M. van (Springer, 2011)
Analog Circuit Design contains the contribution of 18 tutorials of the 19th workshop on Advances in Analog Circuit Design. Each part discusses a specific to-date topic on new and valuable design ideas in the area of analog circuit design. Each part is presented by six experts in that field and state of the art information is shared and overviewed. This book is number 20 in this successful series of Analog Circuit Design, providing valuable information and excellent overviews of: Robust Design, chaired by Herman Casier, Consultant Sigma Delta Converters, chaired by Prof. Michiel Steyaert, Catholic University Leuven RFID, chaired by Prof. Arthur van Roermund, Eindhoven University of Technology Analog Circuit Design is an essential reference source for analog circuit designers and researchers wishing to keep abreast with the latest development in the field. The tutorial coverage also makes it suitable for use in an advanced design course.